2013
DOI: 10.1002/agr.21335
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Innovation Between Food and Manufacturing Firms: An Analysis of Persistence

Abstract: The authors examine the differences in the behavior of the innovation between the Spanish agrifood and manufacturing firms using firm-level data from 1990-2008 to analyze the persistence in innovation and to explore the explanatory determinants of the probability of being product and process innovator. Survival functions, transition probability matrices, and dynamic discrete choice panel data models are combined to measure persistence. The results suggest that in the food industry the persistence of process i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
63
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 47 publications
5
63
0
1
Order By: Relevance
“…However, recent literature revels a dual perspective on the relation between firm size and R&D efforts. As we said previously, some authors detected a positive relation between larger firms and innovation, because of improved access to human, financial resources and profit persistence (Bayona et al,2013;Karantininis et al, 2010;Laforet, 2008;Lin & Lin, 2012;Naranjo-Gil, 2009;Segarra & Arauzo, 2008;Hirch & Gschwandter, 2013;Triguero et al, 2013). On the contrary, other authors underline the ability of SMEs firms to innovate, based on their flexibility, interpersonal communication, etc (Bayona et al, 2001;;O'Regan et al, 2005;Maravelakis et al, 2006;Pla-Barber & Alegre, 2007;Alarcón & Sánchez, 2013).…”
Section: Determinants Of Randd Participationmentioning
confidence: 77%
“…However, recent literature revels a dual perspective on the relation between firm size and R&D efforts. As we said previously, some authors detected a positive relation between larger firms and innovation, because of improved access to human, financial resources and profit persistence (Bayona et al,2013;Karantininis et al, 2010;Laforet, 2008;Lin & Lin, 2012;Naranjo-Gil, 2009;Segarra & Arauzo, 2008;Hirch & Gschwandter, 2013;Triguero et al, 2013). On the contrary, other authors underline the ability of SMEs firms to innovate, based on their flexibility, interpersonal communication, etc (Bayona et al, 2001;;O'Regan et al, 2005;Maravelakis et al, 2006;Pla-Barber & Alegre, 2007;Alarcón & Sánchez, 2013).…”
Section: Determinants Of Randd Participationmentioning
confidence: 77%
“…In particular, although innovation strategies are sector‐specific (Alfranca et al ., ), most of the studies have focused on the manufacturing industry, and empirical evidence on innovation strategies in the agri‐food domain is relatively recent (Hernández‐Espallardo et al ., ; Pascucci et al ., , ; Triguero et al ., ; Ciliberti et al ., ). While the agri‐food sector is generally considered as a low‐tech industry, displaying low innovation intensity (Mark‐Herbert, ; Triguero et al ., ), several authors suggest that innovation processes in the agri‐food industry are becoming more complex, perhaps more than in other sectors (Rama, ; Enzing et al ., ; Alarcón and Sánchez, ; Ciliberti et al ., ). Reasons for this development include the biotechnology revolution, bio‐energy production and distribution, and the increased pressure to maintain better process controls to guarantee food safety, variety and quality.…”
Section: Introductionmentioning
confidence: 99%
“…The question remains, is innovation equally important for artisanal agrifood sectors, which are often regarded as more low-tech (e.g. Triguero et al, 2013). Bianca Kühne (2011) showed that innovations are indeed also important in artisanal sectors, such as Italian cheese and ham, Belgian beer and Hungarian sausages, which were formerly considered as very traditional.…”
mentioning
confidence: 99%